Automation of block assignment planning using a diagram-based scenario modeling method - Hwang In Hyuck; Kim Youngmin; Lee Dong Kun; Shin Jong Gye (International Journal of Naval Architecture and Ocean Engineering, 2014)
Most shipbuilding scheduling research so far has focused on the load level on the dock plan. This is be¬cause the dock is the least extendable resource in shipyards, and its overloading is difficult to resolve. However, once dock scheduling is completed, making a plan that makes the best use of the rest of the resources in the shipyard to minimize any additional cost is also important. Block assignment planning is one of the midterm planning tasks; it assigns a block to the facility (factory/shop or surface plate) that will actually manufacture the block according to the block characteristics and current situation of the facility. It is one of the most heavily loaded midterm planning tasks and is carried out manu¬ally by experienced workers. In this study, a method of representing the block assignment rules using a diagram was su¬ggested through analysis of the existing manual process. A block allocation program was developed which automated the block assignment process according to the rules represented by the diagram. The planning scenario was validated through a case study that compared the manual assignment and two automated block assignment results.